The effect of REACT strategy assisted by GeoGebra software on students' mathematical representation ability - Nurzannah Nurzannah; Muliana Muliana; Herizal Herizal; Fajriana Fajriana; Mursalin Mursalin (Malikussaleh Journal of Mathematics Learning (MJML), 2021)
This study was conducted to determine the effect of REACT strategy assisted by GeoGebra software on students' mathematical representation ability. This study was quasi-experimental with a quantitative approach. The design used in this study was The Nonequivalent Posttest Only Control Group Design. Four posttest questions were given to 25 students of Class VIII A and 25 students of Class VIII B at SMP Negeri Arun Lhokseumawe (public middle school). The data obtained from the posttest results were analyzed by data normality test and data homogeneity test, then hypotheses were tested using a t-test to see the effect of REACT strategy assisted by GeoGebra software on students' mathematical representation ability. The results of the data analysis of the posttest score tested using the t-test, the sig value was obtained. (2-tailed) of 0.000 > 0.05. This showed that there was a significant effect of using the REACT strategy assisted by GeoGebra software on students' mathematical representation ability.